An evacuation model coupling with toxic effect for chemical industrial park. (January 2015) - Shen, Yang; Wang, Qingsong; Yan, Weigang; Sun, Jinhua
Abstract: Emergency evacuation plan plays a key role for disaster management and successful evacuation. In this work, a conceptual decision support system is established and a method to determine the evacuation scope under toxicant leakage accidents is also proposed. Simultaneously, a route selection approach coupling with polluted scope is proposed based on operation mathematic analysis. The best route for evacuee at each location on toxic leakage accidents is the one along with which the heath injury is minimal. Hence, a variable based on toxic load is defined and noted as D V i − V j, which is used to quantify the toxic exposure. The universally minimal D V i − V j is taken as the optimized goal in the model. And then, one case is presented and indicates that this approach can aid the emergency managers to make the right response to the leakage accident in an efficient manner. This new method is also useful for fire risk assessment and design of chemical industrial park. Highlights: A conceptual model of emergency decision system is established. A method to determine the evacuation zone under leakage accidents is reported. A variable ( D V i − V j ) is defined to quantify the injury to evacuees. A new mathematic model is proposed and a case is studied.